Japan - Strauss, Robert; Taylor, Chris and Wheeler, Tony (Australia Lonely Planet Publications)
Provides information on ski resorts in Japan. This guide offers coverage of Okinawa and Southwest islands; including dive spots and beaches. It also includes colour highlights of Japan, chosen by travellers, Lonely Planet staff, and authors.
Include Maps and Colored Illustrations.
Keywords: Japan -- Civilization